2012
DOI: 10.1007/s00441-012-1439-z
|View full text |Cite
|
Sign up to set email alerts
|

Proteases, cystic fibrosis and the epithelial sodium channel (ENaC)

Abstract: Proteases perform a diverse array of biological functions. From simple peptide digestion for nutrient absorption to complex signaling cascades, proteases are found in organisms from prokaryotes to humans. In the human airway, proteases are associated with the regulation of the airway surface liquid layer, tissue remodeling, host defense and pathogenic infection and inflammation. A number of proteases are released in the airways under both physiological and pathophysiological states by both the host and invadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 183 publications
2
30
0
Order By: Relevance
“…#P Ͻ 0.05 vs. complete 5% HDE. 12,23,30,38). In light of the identification of protease activity in a variety of environmental allergens and irritants, it is not surprising that CAFO dust extract was found to contain potentially harmful proteolytic activity as well.…”
Section: Discussionmentioning
confidence: 99%
“…#P Ͻ 0.05 vs. complete 5% HDE. 12,23,30,38). In light of the identification of protease activity in a variety of environmental allergens and irritants, it is not surprising that CAFO dust extract was found to contain potentially harmful proteolytic activity as well.…”
Section: Discussionmentioning
confidence: 99%
“…These studies led to the hypothesis that CFTR has a dual function as anion channel and regulator of ENaC, and provided an explanation how normal airway cells can switch from ENaC-mediated absorption to CFTR-mediated secretion, and why ENaC is hyperactive in CF [9,97]. More recently, it was found that neutrophil elastase (NE), a major neutrophil product, other proteases released from inflammatory cells, as well as bacteria in CF airways, can activate ENaC directly by proteolytic cleavage independent of mutant CFTR [98][99][100][101][102][103].…”
Section: Enacmentioning
confidence: 98%
“…ASL hydration is controlled by the transepithelial movement of ions and water (5,6,17,36). At the apical membrane of airway epithelia, anions are mostly secreted by CFTR and Na ϩ is absorbed by the epithelial sodium channel (ENaC) (5,17,23,33,36). In the case of cystic fibrosis (CF), where CFTR is mutated and has disrupted or diminished function, the balance between anion secretion and Na ϩ absorption is altered (5,6,17,23,36,38).…”
mentioning
confidence: 99%